Evidence of two-channel distortion effects in positronium formation reactions - Macri, Pablo Alejandro (2004)
The formation of ground-state positronium in collisions of positrons on hydrogen-like atoms is considered. In previous theoretical works, two-centre distorted wavefunctions were employed to approximate either the initial or the final channel. Here we report results obtained by means of the eikonal final state continuum distorted wave approximation for which asymptotically correct distorted wavefunctions are used for both the initial and final states of the scattering system. Comparison of the present theoretical total cross sections with experimental data reveals that distortion effects become important in both channels as the impact energy decreases. This work also shows that distortedwave theories may be extended from their usual domain of high impact energies to lower ones.